Folklore of Megibung and Its Digitalization as an Effort to Sustain the Balinese Tradition in the Globalization Era - I Nyoman Adi Susrawan; I Wayan Artika (Soshum: Jurnal Sosial dan Humaniora, 2023)
This research is qualitative descriptive research that aims to (1) describe the elements of humans, nature, and God in the megibung tradition, (2) the relationship between humans, nature, and God in the megibung tradition, (3) describe the transfer of the vehicle for digitising gibing folklore as a type of folklore that is always maintained in the globalisation era. Data collection methods used in this research are documentation, observation (observations in the field), and interviews. The research results show that in the megibung tradition, the elements of humans, God, and nature are interrelated and influence each other. Humans are associated with the presence of God through gratitude and offerings, while the human relationship with nature is reflected in the use of natural resources and awareness of natural balance. This tradition teaches spiritual values, gratitude, and concern for nature as integral to the megibung experience. One of the efforts that can be made so that the gibing tradition remains stable in the digitalisation era is to transfer the vehicle for the gibing tradition from documentation in the form of oral discourse to digitalisation. Through this digital vehicle, people worldwide can get to know and appreciate the richness of Balinese culture and the gibing tradition virtually. It can also be an exciting way to promote tourism and preserve Balinese cultural traditions in the digital age.